Students' Perceptions toward Synchronous Online Learning at the English Department of Universitas Negeri Padang - Pitri Karismanda; Dinovia Fannil Kher (Journal of English Language Teaching, 2022)
This research analyzed students’ perception of synchronous learning through three aspects. The design of the research was descriptiveresearch. To gather the data, semi-structuredinterview guidelines were used as the instrument. The subject or the key informants of this research consisted of 25 students of the K3 year 2020 English Education at Universitas Negeri Padang. The researcher used random cluster sampling to pick out the sample. Data analysis showed that students had positive perceptions in terms of the teaching material and the student interaction aspect. Yet, they had negative perceptions about the aspect of the learning environment. The students claimed, in terms of learning environment, synchronous learning created a monotonous learning atmosphere they felt bored, unfocused and easily distracted. Therefore, it could be concluded that, if among the synchronous learning aspects, one aspect was perceived negatively, there was a possibility that the learning process was not yet optimal. Thus, it was suggested that the learning environment aspect should be given more attention to due to its impact on students’ learning process.